(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
Varietal selection and appropriate placement of nitrogen fertilizer could reduce the magnitude of nitrogen losses to a considerable extent and improve its use efficiency for better grain production. An experiment was carried out during the period from July to December at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh to evaluate the effect of variety and nitrogen fertilizer management on the growth and yield of transplant aman rice. The treatments consisted of three varieties viz. BR11, BRRI dhan49 and Binadhan-7, and five nitrogen fertilizer managements viz. two depth of placement of USG (Urea Super Granule) and three split applications of prilled urea. The experiment was laid out in a randomized complete block design with three replications. The results showed that the effect of variety and nitrogen fertilizer management significantly influenced all the yield contributing characters except weight of 1000- grains, non-effective tillers hill-1 and panicle length. The highest grain yield (3.69 t ha-1) was obtained from Binadhan-7. In the case of nitrogen fertilizer management, the highest grain yield (4.32 t ha-1) was found from the 6 cm depth placement of USG. The highest grain yield (4.82 t ha- 1) was observed from the interaction of Binadhan-7 with the 6 cm depth of placement of USG. It may be concluded that Binadhan-7 with 6 cm depth of placement of USG appeared as the promising practice to maximize the yield of transplant aman rice. Res. Agric., Livest. Fish.8(3): 281-289, December 2021